2020
DOI: 10.3390/bios10060056
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Skin Sensors and Their Challenges: A Review of Transdermal, Optical, and Mechanical Sensors

Abstract: Wearable technology and mobile healthcare systems are both increasingly popular solutions to traditional healthcare due to their ease of implementation and cost-effectiveness for remote health monitoring. Recent advances in research, especially the miniaturization of sensors, have significantly contributed to commercializing the wearable technology. Most of the traditional commercially available sensors are either mechanical or optical, but nowadays transdermal microneedles are also being used for micro-sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 170 publications
0
25
0
1
Order By: Relevance
“…We will generate critical insights on whether consumer-grade wearables that measure hr, activity (steps/day), sleep duration and body shell temperature can be used to generate valid and reliable data on an individual level in low-resource context. Wearable devices can be deemed unreliable, in particular when human activity impedes measurement [ 63 ]. A study has found that substantial differences exist between various devices and various activities, at times showing significantly high average error as compared to measured resting periods [ 64 ].…”
Section: Expected Outcomes Of the Study And Discussionmentioning
confidence: 99%
“…We will generate critical insights on whether consumer-grade wearables that measure hr, activity (steps/day), sleep duration and body shell temperature can be used to generate valid and reliable data on an individual level in low-resource context. Wearable devices can be deemed unreliable, in particular when human activity impedes measurement [ 63 ]. A study has found that substantial differences exist between various devices and various activities, at times showing significantly high average error as compared to measured resting periods [ 64 ].…”
Section: Expected Outcomes Of the Study And Discussionmentioning
confidence: 99%
“…heart rate and oxygen saturation estimation by smart watches, [67]); (ii) sampling interstitial fluids via microneedle (e.g. continuous glucose monitors, [68]); (iii) motion sensors (e.g. ventilation, [69]); or (iv) sampling of eccrine sweat (e.g.…”
Section: Major Barriers To Physiologging Research (A) Internal Logger Placementmentioning
confidence: 99%
“…-Sensing: Sensors are the eyes and ears of wearable devices, measuring mechanical, electrical, chemical, optical, and other signals originating from the body and thus largely defining the utility available from a given device (Bandodkar and Wang, 2014;Nag et al, 2017;Ahmad Tarar et al, 2020;Shi et al, 2020). In the area of sensors, most of the recent progress is driven by advances in Micro-Electro-Mechanical Systems (MEMS) and Nanotechnologies (Jayathilaka et al, 2019).…”
Section: Overviewmentioning
confidence: 99%